Activation and conformational changes of chitinase induced by ultrasound. (1st July 2019) - Hou, Furong; Ma, Xiaobin; Fan, Lihua; Wang, Danli; Wang, Wenjun; Ding, Tian; Ye, Xingqian; Liu, Donghong
Highlights: Chitinase was activated by ultrasound under particular conditions. Ultrasound increased Vmax and decreased Km compared to the untreated chitinase. CD, FTIR, Raman and fluorescence spectra were applied to analyze conformational changes. Ultrasound decreased α-helix and β-turn but increased β-sheet and random coil. Ultrasound altered the microenvironment by reducing tryptophan on chitinase surfaces. Abstract: This study investigated the effect of ultrasound on chitinase activity and conformational changes. Results revealed that ultrasound activated chitinase with a maximum enhancement of 19.17% compared with the untreated chitinase. Furthermore, an increase of Vmax and a decrease of Km after sonication were obtained, illustrating that the affinity between chitinase and substrate was intensified. No obvious effect on the tolerance to most metal ions was exhibited whether sonicated or not (p > 0.05). The conformational changes of chitinase were analyzed by circular dichroism (CD), Fourier transform infrared (FTIR), Raman and fluorescence spectroscopy. Results indicated that the activation of chitinase induced by ultrasound was presumably due to the decrease of tryptophan on the chitinase surface and the increase of β-sheet and random coil in chitinase secondary conformation. In brief, ultrasound is a possible way to activate chitinase to increase its application in food industry.